Gold exploration in tropical and sub-tropical terrains with special emphasis on Central and Western Africa - Breedt, Machiel Christoffel (Rhodes University, Faculty of Science, Department of Geology, 1996)
The aim of this dissertation is an attempt to' provide a general guide for future gold exploration in tropical and sub-tropical terrains. The dissertation includes a brief discussion of the various exploration techniques used in regional and local exploration. This provide the necessary background knowledge to discriminate between the constraints and applications and to be able to select the techniques which are more suitable for gold exploration in tropical and sub-tropical terrains. Weathering, gold geochemistry and soil formation, fields often neglected, are emphasized to illustrate the importance of the mobility and dispersion of gold in the weathering of the lateritic soil profile. A sound knowledge and experience in regolith mapping is to the advantage of the explorationist. Case studies with special emphasis on Central- and Western Africa are included to illustrate the effectiveness of some of the gold exploration techniques in tropical and sub-tropical terrains. Gold exploration is a highly complex and demanding science and to be successfull involves the full intergration of all geological, geochemical and geophysical information available. An intergrated exploration method and strategy would enhance the possibility of making viable discoveries in this highly competative environment where our mineral resources become more depleted every day. Where applicable, the reader is refered to various recommended literature sources to provide the necessary background knowledge which form an integral part of gold exploration.
Keywords: Geochemical prospecting -- Tropics; Geochemical prospecting -- Africa; Gold ores -- Geology -- Tropics; Gold ores -- Geology -- Africa